Who Marries Differently Aged Spouses? Ability, Education, Occupation, Earnings, and Appearance - Mansour, Hani; McKinnish, Terra (The Review of Economics and Statistics, 2014)
In direct contrast to conventional wisdom and most economic models of marital age gaps, we present robust evidence that men and women who are married to differently-aged spouses are negatively selected. Empirical results show lower cognitive ability, lower educational attainment, lower occupational wages, lower earnings, and less attractive appearance among those married to a differently-aged spouse. These results, obtained using samples of first marriages and controlling for age of marriage, are consistent with a model in which individuals with more schooling and more upwardly-mobile occupations interact more heavily with similarly-aged peers and are ultimately more likely to marry similarly-aged spouses.